A laser system for Rubidium in the magneto optical trap. - Muhammad Nur Hidayat Abdul Ghani. (2013)
In this final year project, 2 tunable laser systems are constructed for the purpose of cooling and trapping 87Rb atoms in the Magneto-Optical Trap (MOT). Both lasers are interference- lter stabilized external cavity diode lasers (ECDLs) at 780nm. The power of the cooling laser is ampli ed with the tapered ampli er in the Master Oscillation Power Ampli er (MOPA) con guration. The cooling is locked via the AC locking using the Saturated Absoprtion spectroscopy wheres the second laser, the repumper laser is locked with respect to the cooling laser via trombone locking using beat signal. Acoustic-optic modulators (AOMs) are used to o set and tune the frequency of the various beams required for the experiment. The cooling laser system will then be paired with a Zeeman slower which acts as a precooler before loading the atoms into the MOT. The experimental realization is also explained, with the critical components of the experiments such as the electronics and the optics mentioned.